Smart and sassy : the strengths of inner city Black girls - Stevens, Joyce West, 1936- (Oxford University Press, 2002)
Empirically based, the daily experiences of adolescent black females is explicated within an explanatory model of social context and developmental theory. The author argues that adolescence must be seen from strength and health perspectives.
Keywords: African American teenage girls -- Attitudes.; African American teenage girls -- Psychology.; African American teenage girls -- Social conditions.; Adolescence -- United States.; Adolescentes noires américaines -- Attitudes.; Adolescentes noires américaines -- Psychologie.; Adolescentes noires américaines -- Conditions sociales.; Adolescence -- États-Unis.; FAMILY & RELATIONSHIPS -- Life Stages -- Adolescence.; FAMILY & RELATIONSHIPS -- Life Stages -- Teenagers.; Adolescence; African American teenage girls -- Attitudes; African American teenage girls -- Psychology; African American teenage girls -- Social conditions; United States